Combined microwaves and fractional microablative CO2 laser treatment for postpartum abdominal laxity. (18th June 2020) - Bonan, Paolo; Verdelli, Alice
Abstract: Background: Postpartum abdominal changes represent a major esthetic concern affecting women. As the abdomen stretches during pregnancy and some of the muscles lose tone, there is an increased skin laxity and a loss of abdominal elasticity. As a result, the abdomen becomes saggy. Aims: To evaluate the performance of a combined microwaves and fractional microablative CO2 laser treatment for reshaping and improvement of abdomen texture/laxity and striae distensae in postpartum women. Patients/Methods: Fifteen women (median age 38 years) received three monthly abdomen treatments with a new microwaves platform, the ONDA Coolwaves ® (DEKA) system, followed by a treatment with fractional microablative CO2 laser (SmartXide2; DEKA) a month thereafter. We followed up each patient's weight and nutritional habits. Outcome was assessed using reproducible circumference and abdominal measurements, digital and 3D photography, the laxity score as well as patient satisfaction index. Results: The overall mean circumferences reduction was 3.6 ± 1.2 cm. Significant improvement in skin laxity and tightening was noted by physicians and patients as well as a reduction of striae distensae. Interestingly, as a result of skin remodeling, repositioning of the umbilicus was also demonstrated. Treatments were well tolerated with no side effects. Conclusions: Our data showed a sustainable reduction in circumference and improvement in appearance of abdomen in postpartum women, without compromising patients' safety.